Naringenin alleviates myocardial ischemia/reperfusion injury by regulating the nuclear factor-erythroid factor 2-related factor 2 (Nrf2) /System xc-/ glutathione peroxidase 4 (GPX4) axis to inhibit ferroptosis. Issue 2 (20th December 2021) - Xu, Shujun; Wu, Bingxin; Zhong, Biying; Lin, Luoqi; Ding, Yining; Jin, Xiao; Huang, Zhiwei; Lin, Miaoyang; Wu, Huanlin; Xu, Danping
ABSTRACT: Ferroptosis is an important form of myocardial cell death in myocardial ischemia-reperfusion injury (MIRI). Naringenin (NAR), as a flavonoid, has a significant advantage in improving MIRI. But the regulatory effect and mechanism of NAR on ferroptosis in MIRI have not been reported. After the rats were given NAR and induced to form myocardial ischemia-reperfusion (MI/R) injury, Tetrazolium chloride (TTC) staining was used to detect the myocardial infarction area of rats, and Hematoxylin-eosin (H&E) staining was used to detect myocardial injury. The markers of tissue inflammation were detected by ELISA. Serum creatine kinase Serum creatin kinase (CPK), Lactate dehydrogenase (LDH), and lipid peroxide (LPO) and oxidative stress related levels were measured. In addition, iron detection kits were used to detect total iron and Fe 2+ levels in cardiac tissues, and western blot was used to detect the expression of ferroptosis-related proteins and the expression of nuclear factor-erythroid factor 2-related factor 2 (Nrf2) and glutathione peroxidase 4 (GPX4). At the cellular level, H9C2 cardiomyocytes were induced by hypoxia/reoxygenation (H/R), and ferroptosis inducer Erastin was administered to detect cell viability, ferroptosis-related indicators, oxidative stress related indicators, and expressions of Nrf2 and GPX4, to explore the mechanisms involved. NAR alleviated MI/R-induced pathological damage, inflammation and lipid peroxidation in myocardial tissue of rats. NAR adjusted the NRF2 /System xc – /GPX4 axis and improved ferroptosis. At the cellular level, ferroptosis inducer Erastin reversed the protective effect of NAR on H/R-induced H9C2 cardiomyocytes. In conclusion, NAR can alleviate MIRI by regulating the Nrf2/System xc-/GPX4 axis to inhibit ferroptosis.